Viceregal hospitals in Lima - Villamón, Juan (2023)
Health and hygiene are distinctive features in modern societies. These concerns, about new issues of public interest, brought consequences and manifestations in Peru during the colonial era. Hospital architecture reflected a new awareness to face health issues, strongly impregnated with a religious character. The care of the sick was organized separating some from others, in a context of great social differences. Within the planned changes, at the level of spatial organization, there was a cross-shaped plant typology, which was developed in different countries, including Peru. In the city of Lima, unfortunately, most of the hospitals from the colonial era have been destroyed, without any attempt to preserve them.